Vida camponesa, alimentos orgânicos, fortalecimento identitário sociocultural e territorial: estudo de caso na comunidade Olhos D’água e Assentamento Carinhosa em Uberlândia-MG, Brasil - Zuffi, Mônica Arruda (2023)
This research investigates how families in the rural communities of Olhos D'Água and the Carinhosa Settlement in the municipality of Uberlândia-MG develop socio-productive systems that prioritize ways of sharing knowledge and practices, promoting crops free from pesticides and agrochemicals, such as organic production and agroforestry systems. It analyzes the interaction between peasants and the cycles of nature and symbiotic relationship that contains an immense range of strategies shaped by traditional knowledge, built over a lifetime. It also elucidates the constant ways to overcome marketing and environmental setbacks, as well as knowledge that gives them autonomy to face these challenges. The importance and relevance of this study lies in the need to present how peasants maintain sustainable and regenerative practices in a context dominated by conventional agriculture and the logic of agribusiness. This research is relevant to highlight viable alternatives for food production that are not subject to the logic of agroindustry, promoting the autonomy, identity and resilience of rural communities. The general objective of this research is to explain, based on the initiative of the peasant family, the relevance of the social network in the exchange of experiences and solidarity, analyzing how organic production and the use of agroforestry systems occur in a space homogenized by the logic of agribusiness. Furthermore, we seek to understand the contradictions, tensions and new socio-productive arrangements that emerge as forms of resistance and existence in the face of adversity. The central problem of this research lies in the implementation and maintenance of agroecological practices that challenge the predominant logic of agribusiness, promoting sustainable and agrochemical-free production systems in rural communities such as Olhos D’Água and Assentamento Carinhosa.The research adopted a dialogical and qualitative approach, divided into two main stages: a Non- Systematic Literature Review and a Case Study in the communities. The qualitative bibliographic review involved the analysis of different types of academic publications and documents on the topic. The case study followed the steps: formulating questions, observing agricultural practices, and semi-structured interviews with farmers in Uberlândia-MG. Data collection included community visits and interviews to understand farmers' perceptions. The data was analyzed using Thematic Content Analysis, identifying and interpreting thematic categories based on the participants' reports. The main theoretical bases of this research include studies on agroecology, peasant socio-productive systems, regenerative practices and sustainable management of natural resources, emphasizing the leading role of rural communities in maintaining their practices and identity in the face of the impositions of agribusiness.